Evaluation Categories in Private and Public Law: Problems of their Application and Interpretation - ANISIMOV, Aleksey Pavlovich; KOZLOVA, Marina Yurievna; RYZHENKOV, Anatoly Yakovlevich (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
The article presents research in the role and significance of evaluation categories in the legal system. It is proved that presence of evaluation categories is unavoidable for a legal system of any country of the world. In terms of Russia the authors show a different role and significance of evaluation categories in the branches of private, public and combined public and private law. Meanwhile, if in the branches of private law the evaluation categories are interpreted only by the court, in the branches of public law the role of interpretation of evaluation categories by the governmental authorities is more significant. The drawn conclusions may be used in the course of further scientific research in evaluation categories in various branches of law (including comparative legal investigations), as well as in practice of the business community representatives within their activities in Russia.
Keywords: evaluation categories; private and public law; interpretation; legal activities; unfair competition